Surface Modification of Electrospun Bioresorbable and Biostable Scaffolds by Pulsed DC Magnetron Sputtering of Titanium for Gingival Tissue Regeneration; Polymers; Vol. 14, iss. 22 - Badaraev A. D. Arsalan Dorzhievich; Sidelev D. V. Dmitry Vladimirovich; Kozelskaya A. I. Anna Ivanovna; Bolbasov E. N. Evgeny Nikolaevich; Tran Tuan Hoang; Nashchekin A. V. Alexey; Malashicheva A. B. Anna; Rutkowski S. Sven; Tverdokhlebov S. I. Sergei Ivanovich (2022, 2022)
In this study, polymer scaffolds were fabricated from biodegradable poly(lactide-co-glycolide) (PLGA) and from non-biodegradable vinylidene fluoride-tetrafluoroethylene (VDF-TeFE) by electrospinning. These polymer scaffolds were subsequently surface-modified by sputtering titanium targets in an argon atmosphere. Direct current pulsed magnetron sputtering was applied to prevent a significant influence of discharge plasma on the morphology and mechanical properties of the nonwoven polymer scaffolds. The scaffolds with initially hydrophobic properties show higher hydrophilicity and absorbing properties after surface modification with titanium. The surface modification by titanium significantly increases the cell adhesion of both the biodegradable and the non-biodegradable scaffolds. Immunocytochemistry investigations of human gingival fibroblast cells on the surface-modified scaffolds indicate that a PLGA scaffold exhibits higher cell adhesion than a VDF-TeFE scaffold.